Model Pembelajaran Berbasis Masalah Berbantuan Simulasi Komputer untuk Meningkatkan Keterampilan Berpikir Kritis Calon Guru Fisika - Lovy Herayanti; Habibi Habibi (Department of Physics Education, Universitas Mataram, 2015)
This study aims to examine the effectiveness of the applying of problem-based learning with computer simulation toward the critical thinking skills of pre-service physics teachers. This is necessary because critical thinking skills do not develop without the explicit and deliberate effort invested in its development. The combination with computer simulations are considered essential to overcome the difficulties learn abstract concepts in physics. This is research an experimental research. The subjects of this study were students at the Department of Physics Education, FPMIPA IKIP Mataram. The research instruments are test of critical thinking skills and questionnaire. The results showed a significant difference between students' critical thinking skills experimental class and control class, where an increase in the experimental class is higher than the control class. Students also gave a positive response to a given model.